2006
DOI: 10.1093/eurheartj/ehl411
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with intracoronary adenosine reduces the incidence of myonecrosis after non-urgent percutaneous coronary intervention: a prospective randomized study

Abstract: Pretreatment with 50 microg of adenosine decreases the incidence of myonecrosis after non-urgent PCI compared with that without pretreatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 34 publications
1
32
2
1
Order By: Relevance
“…21,22 Nicardipine has been used prophylactically as an intragraft infusion to prevent no-reflow in patients undergoing elective SVG-saphenous venous graft. 23 Unlike studies with other vasodilators such as intravenous potassium channel activator, nicorandil, 24 intracoronary verapamil, 25 and adenosine, 26 pretreatment with intracoronary nicardipine in patients undergoing elective PCI showed no statistically significant benefit in our study. This could be due to differences in the patient population, differences in the baseline characteristics of the 2 groups, and low overall incidence of myocardial necrosis seen in our study.…”
Section: Discussionmentioning
confidence: 51%
“…21,22 Nicardipine has been used prophylactically as an intragraft infusion to prevent no-reflow in patients undergoing elective SVG-saphenous venous graft. 23 Unlike studies with other vasodilators such as intravenous potassium channel activator, nicorandil, 24 intracoronary verapamil, 25 and adenosine, 26 pretreatment with intracoronary nicardipine in patients undergoing elective PCI showed no statistically significant benefit in our study. This could be due to differences in the patient population, differences in the baseline characteristics of the 2 groups, and low overall incidence of myocardial necrosis seen in our study.…”
Section: Discussionmentioning
confidence: 51%
“…The potential pretreatment role of propranolol [21], adenosine [22], omega-3 [23], and cyclosporine A [24] in the prevention of PMI has been also shown by several studies.…”
Section: Discussionmentioning
confidence: 84%
“…Several mechanisms are involved in the development of this type, which include the distal embolisms of atheromatous plaque and thrombotic components during angioplasty, platelet activation and thrombosis formation as a result of the activation of coagulation factors, neurohormonal activation and coronary vasospasm, the oxidative stress which is identified by elevation of some biomarkers such as isoprostane-PG(F2) Alfa and ischemia-modified albumin, and finally, inflammation which is recognized by raising of inflammatory biomarkers such as IL-6 and CRP during angioplasty [7]. Given the mechanistic basis of PMI, a large number of studies have investigated the potential benefits of some medications as a cardioprotective agent in the prevention of PMI [15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Results from a small study involving 28 patients suggested that adenosine infusion may reduce the occurrence of myonecrosis after nonurgent PCI. In a prospective randomized study, we found that pretreatment with 50 lg of adenosine decreases the incidence of myonecrosis from 39% to 13% after PCI to de novo native coronary arteries, compared to standard PCI without pretreatment [16]. In patients undergoing urgent reperfusion therapy for acute myocardial infarction, early studies suggested that adenosine infusions may reduce heart muscle damage.…”
Section: Adenosinementioning
confidence: 94%